Analysis the role of m-Health technology on psychological development of Bangladesh using TAM & UTAUT - Binte-Saif, Samira (BOHR International Journal of Advances in Management Research, 2025)
In Bangladesh (BD), mental health issues are prevalent, affecting across various ages and social statuses. Common mental health problems include depression, anxiety, and suicidal tendencies, often arising from factors such as family issues, joblessness, relationship troubles, and dowry-related problems. Studies indicate that the frequency of mental health issues in Bangladeshi people varies, but women are more likely to be affected than men. Sound mental health is a crucial determinant for a stable and fruitful life. In order to prevent mental health problem of BD, various mobile health (m-Health) technologies have emerged, offering essential services that help reduce healthcare disparities and enhance perceived health. The market for m-Health technology in BD is growing, and this paper aims to illustrate the impact of m-Health technology on the mental health development in the country using technology acceptance model. It also examines various factors related to psychological development in BD and the attitudes of respondents toward m-Health technology.